Ligninolytic enzymes from marine-derived fungi: production and applications - Sette, Lara Duraes [UNESP]; Bonugli Santos, Rafaella Costa; Trincone, A. (Woodhead Publ Ltd, 2013)
The demand for microbial industrial enzymes is ever-increasing due to their use in a wide variety of processes. Ligninolytic enzymes play a crucial role in the global carbon cycle. One of the most important current applications of these enzymes is in the environmental remediation domain, in processes in which biological systems are used to degrade or neutralize pollutants or to decolorize dyes. Taking into account that much environmental pollution occurs in saline conditions, the use of marine-derived fungal enzymes can be considered strategic, since these micro-organisms are adapted to the marine ecosystem.
Keywords: marine fungi; ligninolytic enzymes; biotechnological applications; biodegradation; bioremediation